Inflation and Wage Expectations of Firms and Employees - Lukas Buchheim; Sebastian Link; Sascha Möhrle (Institute of Labor Economics (IZA), 2024)
We study the link between expected inflation and wages using novel panel data from German firms and employees. We find that pass-through—the percentage point change in wage growth given a one percentage point change in expected inflation—is small: 0.11–0.17 for firms and 0.03–0.07 for employees. Utilizing variation in the coverage length of collective agreements, we estimate that passthrough at the intensive margin is 1.4-2 times larger than average pass-through, highlighting the importance of wage rigidities for pass-through. Pass-through also rises with the bargaining power of employees. At the extensive margin, expected inflation has little effect on additional wage negotiations.
Keywords: E24; E31; D84; 330; wage expectations; inflation; pass-through; wage-price spirals; bargaining; firms; employees; survey data